2017
DOI: 10.1063/1.4995965
|View full text |Cite
|
Sign up to set email alerts
|

Elevated transition temperature in Ge doped VO2 thin films

Abstract: A metal-insulator transition study of VO 2 thin films grown on sapphire substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 45 publications
(60 reference statements)
5
51
1
1
Order By: Relevance
“…We then predict that by controlling the amount of Ge doping, we can control the phase‐change temperature. A calculation of the total energy with the non‐magnetic and AFM spin ordering finds that the energy difference between the metallic and non‐metallic phases increases slightly, equivalent to a rise in transition temperature, as observed experimentally …”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…We then predict that by controlling the amount of Ge doping, we can control the phase‐change temperature. A calculation of the total energy with the non‐magnetic and AFM spin ordering finds that the energy difference between the metallic and non‐metallic phases increases slightly, equivalent to a rise in transition temperature, as observed experimentally …”
Section: Resultssupporting
confidence: 58%
“…The spin‐pairing is weakened as a result of the overall spatial separation of V, thus reducing the gap to 0.78 eV. Krammer shows that the transition temperature can be raised by Ge doping, indicating the magnetic ground state energy is lower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from understanding the physics of pure VO 2 , for applications it is of interest to vary the band gap of the insulating phase and vary the phase-transition temperature, while keeping the ability to switch between phases [22][23][24]. For instance, it is useful to shift the transition temperature T C towards room temperature to enhance its suitability as a smart-window coating, or to raise the T C to favor its use as a robust electrical or optical switch.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it is found that alloying VO 2 with MgO will widen its p-d band gap to 2.3 eV for alloying fraction n = 19% [22,23], whereas alloying VO 2 with GeO 2 will raise * jr214@cam.ac.uk its T C [24]. However, so far there is little explanation of these effects in terms of electronic structure.…”
Section: Introductionmentioning
confidence: 99%